Efektifitas Pelatihan Online Di Balai Besar Pelatihan Pertanian (BBPP) Batangkaluku - Andi Amal Hayat Makmur; Agunawan Agunawan (STMIK AKBA, 2021)
Online training is an innovation in the field of education to answer the challenges of the presence of more varied learning methods even without having to meet in person. Some experts argue that online learning (full through the network) has some advantages obtained but there are also some problems in its implementation and also in achieving the objectives of the training that still require further research. This research aims to find out the effectiveness of the implementation of online training conducted by BBPP Batangkaluku. The method used is to use a survey method in the form of online questionnaires for 235 alumni participants of online training organized by BBPP Batangkaluku, but obtained 214 respondents who filled out this questionnaire. Data obtained through the filling of questions by respondents in the form of google form. The results showed that 77.10% of respondents considered that inadequate internet network is a problem in the implementation of online training. 94.86% of respondents felt that they had gained an increased understanding of the substance of the training material. 78.50% did not feel a touch of attitude change, and 80.84% of respondents felt unable to practicalally implement the substance of learning obtained in online training.